Kajian Psikolinguistik: Gangguan Berbahasa pada Anak Autisme - Mifta Kusriyah; Julianita Julianita; Yuyun Yuyun; Fatmawati Fatmawati (UIR Press, 2023)
Psycholinguistics is the science of how human psychological and neurological factors are relate when acquiring, learining, understanding and using language. In the field of psycholinguistics there is a study of language disorder. Language disorder is an obstacle that involves languageprocessing and is experienced by an individual, one of whom is experiencing an autistic spectrum. This will cause disturbances in social, behavioral, and linguistic aspects. In this study using the literature study method, nameky by tracing and obtaining data from journals, books, and orther references that are considered relevant to the research topic. The result of this study found that many Indonesian children with autism have difficulty communicating.